Carbon Emission Intensity, Good Corporate Governance, and Corporate Sustainability: Implications for Low-Carbon Regional Development - Romdhon, Mochamad; Fadilah, Resmi Afifah; Anggraeni, Windi Ariesti; Kartiko, Erik (Badan Perencanaan Pembangunan Kota Malang, 2026)
Low-carbon regional development requires reliable environmental information and effective governance mechanisms, particularly in carbon-intensive sectors. This study examines the relationship between Carbon Emission Intensity and Corporate Sustainability and investigates the moderating role of Good Corporate Governance (GCG) in Indonesia’s energy sector. Employing a quantitative explanatory approach, the study analyzes panel data from 29 energy-sector companies listed on the Indonesia Stock Exchange during 2021–2023 using panel-data regression. Carbon Emission Intensity represents firm-level carbon performance, while Good Corporate Governance reflects organizational oversight capacity. The results indicate that Carbon Emission Intensity is negatively associated with Corporate Sustainability at the 10% significance level. The positive interaction coefficient further suggests that Good Corporate Governance mitigates the adverse relationship between Carbon Emission Intensity and Corporate Sustainability, although the empirical evidence remains moderate rather than conclusive. This study contributes to the environmental accounting literature by integrating carbon-performance measurement, governance oversight, and Corporate Sustainability within a single empirical framework. From a policy perspective, firm-level carbon and governance information can complement regional emissions monitoring, green public procurement, investment screening, and low-carbon development planning. The findings provide an empirical foundation for strengthening the integration of corporate environmental accountability into regional low-carbon development strategies.